Centralized Report Verification and Monitoring in Waste Bank Management: A Web-Based Information System Case Study at the Environmental Agency of Tegal City - Rachma Fadilah Kurnianto; Mohammad Humam; Bayu Aji Santoso (Journal of Information Systems and Technology Research, 2026)
Waste bank data management at the Environmental Agency of Tegal City relied on Google Forms, spreadsheet recapitulation, and manual report compilation, causing data duplication, incomplete reports, inconsistent records, and delayed monitoring; of 187 registered waste bank units, only about 30% submitted monthly reports consistently, and recapitulation took one to two weeks. Previous waste bank information systems mainly supported single-unit operations such as transaction recording and internal reporting, leaving a gap in how a public authority could centrally verify and monitor data from many decentralized units. This study addressed that gap by developing BASMAN, a web-based Waste Bank Management Information System built using the Waterfall approach, integrating master data, operational data, monthly reports, report verification, monitoring, notifications, and data export in one centralized platform with role-based access for administrators and waste bank managers. Unlike prior systems that treated data submission and acceptance as a single step, BASMAN introduced a dedicated agency-level verification stage before report approval. Blackbox Testing confirmed all 35 scenarios passed successfully, and User Acceptance Testing yielded an average score of 4.21 (84.29% acceptance), categorized as highly feasible, demonstrating that BASMAN was both functionally sound and well accepted by its intended users.